Observation of gapped Dirac cones in a two-dimensional Su-Schrieffer-Heeger lattice - Daiyu Geng; Hui Zhou; Shaosheng Yue; Zhenyu Sun; Peng Cheng; Lan Chen; Sheng Meng; Kehui Wu; Baojie Feng (Nature Communications, 2022)
The Su-Schrieffer-Heeger (SSH) model is a prototypical model of topological states, initially proposed to describe spinless electrons on a one-dimensional (1D) dimerized lattice. Here, the authors realize a 2D SSH model in a rectangular lattice of silicon atoms on a silver substrate, observing gapped Dirac cones by angle-resolved photoemission spectroscopy.